Analysis of Factors Affecting the Competitiveness of Indonesian Crude Palm Oil (CPO) Export in the Global Market - Yanita, Mirawati; Napitupulu, Dompak MT; Rahmah, Karina (Indonesian Journal of Agricultural Research, 2019)
This study aims to: (1) Analyze the development of Indonesian CPO export competitiveness in the global market from 1998 to 2017 (2) Analyze factors affecting the competitiveness of Indonesian CPO export in the global market from 1998 to 2017. The data used is time series spanning 20 years (1998-2017). The competitiveness of Indonesian CPO export in the global market is presented descriptively in the form of images, while affecting factors are analyzed using a multiple linear regression model. The results show that Indonesian CPO has comparative and competitive competitiveness in the global market. The results of multiple linear regression tests indicate that the factors that comparatively affect the competitiveness of Indonesian CPO exports in the global market are domestic CPO production, global CPO prices and petroleum prices while factors that competitively affect competitiveness are ​​oil palm plantation area, Malaysian export volume, soybean oil price and exchange rates. Factors that positively impact Indonesian CPO competitiveness are domestic CPO production, oil prices and the ​​oil palm plantation area. Improving these variables will increase the competitiveness of Indonesian CPO exports, while an increase in global CPO prices, soybean oil prices and the exchange rate will reduce the competitiveness of CPO exports. The variable that has no significant effect is the export volume of Malaysia.